Rotational Atherectomy Plus Drug-Coated Balloon Angioplasty for the Treatment of Total In-Stent Occlusions in Iliac and Infrainguinal Arteries. (June 2019) - Milnerowicz, Artur; Milnerowicz, Aleksandra; Kuliczkowski, Wiktor; Protasiewicz, Marcin
Purpose: To analyze the long-term outcomes of a hybrid treatment method combining rotational atherectomy with drug-coated balloon (DCB) angioplasty in patients with total in-stent occlusion in the iliac and/or infrainguinal arteries.Materials and Methods: Between April 2014 and June 2017, 74 consecutive patients (mean age 66.7±9.7 years; 49 men) with total occlusion of a previously implanted stent underwent endovascular recanalization using the Rotarex system and DCB angioplasty. Half (37, 50%) of the patients had critical limb ischemia (CLI), and 30 (41%) of the procedures were performed in emergency. Mean lesion length was 22±15 cm.Results: Overall procedure success was achieved in 73 (98.6%) patients. Six (8.1%) CLI patients developed distal embolism that responded to thrombolysis. Three (4.1%) dissections did not require treatment, while 1 (1.4%) perforation necessitated stent-graft implantation. In all, 33 (44.6%) patients had an additional stent implanted, mainly due to a suboptimal outcome (n=28) or complications (n=5 including the stent-graft). The restenosis rate assessed by duplex ultrasound at 12 months was 20.5% (15/73); 4 (5.5%) patients underwent target lesion revascularization. Recurrent restenosis was more frequent in patients with Rutherford category 5 ischemia (p=0.005), in emergency procedures (p=0.021), after extensive procedures involving 3 independent vessel segments (p=0.016), and if a complication arose during the procedure (p<0.001). In multivariate analysis, only occurrence of a procedural complication was an independent predictor of recurrent restenosis at 1 year (OR 63.3, 95% CI 5.7 to 701.5).Conclusion: These findings imply that rotational atherectomy and DCB angioplasty may provide satisfactory outcomes in the treatment of total in-stent occlusion, with a satisfactory recurrent restenosis rate at 12 months.